2022
DOI: 10.1161/strokeaha.121.038659
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives, Hormone Replacement Therapy, and Stroke Risk

Abstract: BACKGROUND: Millions of women worldwide use exogenous hormones as oral contraceptives or hormone replacement therapy. Still, time-dependent and long-term consequences of exogenous hormones on stroke risk remains unclear. METHODS: We examined the association between self-reported oral contraceptive and hormone replacement therapy use and stroke risk in 257 194 women from the UK Biobank, born between 1939 and 1970. Outcomes included any type of stroke, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 58 publications
1
22
0
1
Order By: Relevance
“…In our cohort, OC use was significantly associated with the risk of ischemic stroke, as has been reported previously. [1][2][3] Importantly, the odds ratio for ischemic stroke associated with OC-use was highest in the tertile with highest genomic risk of ischemic stroke. The formal test of interaction, although not statistically significant, is consistent with our hypothesis that the genomic risk score modifies the association of OC use with ischemic stroke.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In our cohort, OC use was significantly associated with the risk of ischemic stroke, as has been reported previously. [1][2][3] Importantly, the odds ratio for ischemic stroke associated with OC-use was highest in the tertile with highest genomic risk of ischemic stroke. The formal test of interaction, although not statistically significant, is consistent with our hypothesis that the genomic risk score modifies the association of OC use with ischemic stroke.…”
Section: Discussionmentioning
confidence: 95%
“…4 While many of the cardiovascular risk factors such as hypertension and diabetes often emerge by increasing age, the risk for ischemic stroke is suggested to be highest shortly after initiation of OCs. 2 If a genomic risk score could identify women at latent risk, this could help to reduce the burden of early onset ischemic stroke and associated socioeconomic consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the time-varying analysis showed an increased hazard of any stroke in the first year of OC use (HR, 2.49 [95% CI, 1.44–4.30]), with no difference in stroke risk between users and nonusers during the remaining years of use and after discontinuation. 18…”
Section: Is the Timing Of Stroke Events After Starting Oral Contracep...mentioning
confidence: 99%
“…Ample literature has shown that longterm exposure to HRT or OC affects blood clotting, lipid and lipoprotein metabolism, and endothelial function [5]. In contrast, a recent study shows that both OC use and HRT were associated with an increased risk of stroke, especially during the first year of use, possibly due to immediate changes in hemostatic balance [6]. It is also documented that OC exposure makes females more susceptible to stress hormone effects on episodic memory, fear conditioning, and cognitive emotion regulation [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%